2004
DOI: 10.1002/pmic.200300845
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of mitochondrial proteins in cardiomyocytes from chronic stressed rat

Abstract: Chronic restraint stress induces cardiac dysfunction as well as cardiomyocyte injury including severe ultrastructural alteration and cell death, but its mechanism and molecular basis remain unclear. Mitochondria play a key role in regulating cell life. For exploring mitochondrial proteins which correlate with stress-induced injury, two-dimensional electrophoresis and matrix-assisted laser desorption/ionization mass spectrometry (MALDI-TOF MS) were applied. After comparing the protein profiles of myocardial mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…In our previous study, we found that the PHB content in mitochondria increased in apoptotic cardiomyocytes induced by restraint stress (Liu et al 2004). To determine whether PHB played a role in regulating the cardiomyocyte apoptosis induced by H 2 O 2 intervention, the apoptotic rate of cardiomyocytes treated with 200 μM H 2 O 2 for 12 h was examined by flow cytometry.…”
Section: Overexpression Of Prohibitin Inhibits Oxidative Stress-inducmentioning
confidence: 96%
See 1 more Smart Citation
“…In our previous study, we found that the PHB content in mitochondria increased in apoptotic cardiomyocytes induced by restraint stress (Liu et al 2004). To determine whether PHB played a role in regulating the cardiomyocyte apoptosis induced by H 2 O 2 intervention, the apoptotic rate of cardiomyocytes treated with 200 μM H 2 O 2 for 12 h was examined by flow cytometry.…”
Section: Overexpression Of Prohibitin Inhibits Oxidative Stress-inducmentioning
confidence: 96%
“…Recently, Vessal and colleagues have found that PHB existing in extracellular fluid of cultured adipocytes can be translocated to mitochondria and modulates mitochondrial fuel metabolism by inhibition of pyruvate carboxylase (Vessal et al 2006). Previous studies in our laboratory (Liu et al 2004) using proteomics technology have found PHB expression in mitochondria increased dramatically when cardiac structures and functions were injured by chronic restraint stress. However, the function of PHB in cardiomyocytes is still far from clear.…”
Section: Introductionmentioning
confidence: 94%
“…Whereas there is no literature concerning phosphorylation of CPT2, it is known that phosphorylation of CPT1 occurs and that phosphorylation increases CPT1 activity (66). CPT2 activity decreased in rat heart after chronic stress (78), but its association with responses to severe hemorrhage has not been documented.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we observed cardiovascular function disruption and pathological alterations in the electrocardiograms of chronically restraint-stressed rats (Wang et al 2009). Cardiomyocyte damage is considered to be an important cellular basis for stress-induced cardiovascular injury and disease (Liu et al 2004). However, the mechanism of stress-induced cardiomyocyte injury remains unclear.…”
Section: Discussionmentioning
confidence: 99%